Impact of expiratory strength training in amyotrophic lateral sclerosis. Issue 1 (3rd March 2016) - Plowman, Emily K.; Watts, Stephanie A.; Tabor, Lauren; Robison, Raele; Gaziano, Joy; Domer, Amanda S.; Richter, Joel; Vu, Tuan; Gooch, Clifton
ABSTRACT: Introduction : We evaluated the feasibility and impact of expiratory muscle strength training (EMST) on respiratory and bulbar function in persons with amyotrophic lateral sclerosis (ALS). Methods : Twenty‐five ALS patients participated in this delayed intervention open‐label clinical trial. Following a lead‐in period, patients completed a 5‐week EMST protocol. Outcome measures included: maximum expiratory pressure (MEP); physiologic measures of swallow and cough; and penetration–aspiration scale (PAS) scores. Results : Of participants who entered the active phase of the study ( n = 15), EMST was well tolerated and led to significant increases in MEPs and maximum hyoid displacement during swallowing post‐EMST ( P < 0.05). No significant differences were observed for PAS scores or cough spirometry measures. Conclusions : EMST was feasible and well tolerated in this small cohort of ALS patients and led to improvements in expiratory force‐generating pressures and swallow kinematics. Further investigation is warranted to confirm these preliminary findings. Muscle Nerve 54 : 48–53, 2016